Fighting for a Mare Clausum and Secret Science: France, England and Spain in the Strategies of Ambassador Dantas (1557-1568) (Vegueta: Anuario de la Facultad de Geografía e Historia, 2023)
The Portuguese ambassador to France and England during the 1560s, João Pereira Dantas, played a decisive role in Portuguese attempts to sabotage French and English expeditions to the Portuguese Mare Clausum. Studying Dantas’ correspondence, and comparing it with Spanish, French and English sources and studies, this article proposes that tied to traditional policies of Mare Clausum, there was also an attempt at “secret science”, intended to prevent Portuguese nautical experts from serving England and France. The study of Dantas’ maritime espionage shows that Portuguese cosmographical knowledge played a key role in Elizabethan England’s and Valois France’s maritime expeditions in the 1560s.